Measurement of Nanometre-Scale Gate Oxide Thicknesses by Energy-Dispersive X-ray Spectroscopy in a Scanning Electron Microscope Combined with Monte Carlo Simulations - Thomas Walther (Nanomaterials, 2021)
A procedure based on energy-dispersive X-ray spectroscopy in a scanning electron microscope (SEM-EDXS) is proposed to measure ultra-thin oxide layer thicknesses to atomic scale precision in top-down instead of cross-sectional geometry. The approach is based on modelling the variation of the electron beam penetration depth and hence the depth of X-ray generation in the sample as a function of the acceleration voltage. This has been tested for the simple case of silica on silicon (SiO2/Si) which can serve as a model system to study gate oxides in metal-on-semiconductor field-effect transistors (MOS-FETs). Two possible implementations exist both of which rely on pairs of measurements to be made: in method A, the wafer piece of interest and a reference sample (here: ultra-clean fused quartz glass for calibration of the effective k-factors of X-ray lines from elements O and Si) are analysed at the same acceleration voltage. In method B, two measurements of the apparent O/Si ratio of the same wafer sample need to be made at different acceleration voltages and from their comparison to simulations the SiO2 layer thickness of the sample can be inferred. The precision attainable is ultimately shown to be limited by surface contamination during the experiments, as very thin carbonaceous surface layers can alter the results at very low acceleration voltages, while the sensitivity to ultra-thin surface oxides is much reduced at higher acceleration voltages. The optimal operation voltage is estimated to lie in the range of 3–15 kV. Method A has been experimentally verified to work well for test structures of thin oxides on Si-Ge/Si.